The current diagnostic approach to the problem sensorineural hearing loss - G.B. Davronova, N.J. Khushvakova (International Journal of Advanced Science and Technology, 2020)
The data obtained in the course of this study made it possible to increase the number of families for which it was not previously possible to determine the hereditary component in the diagnosis of nonsyndromic sensorineural deafness. In addition, molecular screening of all persons from families weighed down by acquired deafness will reduce the number of defects in sound perception, and patients will be allowed to begin rehabilitation measures at the earliest possible dates to ensure full social adaptation of such patients.